Vincetoxicum pingtaoanum (Apocynaceae: Asclepiadeae), a new species from the Three Gorges District in Central China - Zhang, Cai-Fei; Wang, Yan; Chen, Feng; Zhou, Hou-Lin; Liao, Miao; Odago, Wyclif Ochieng; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2022)
Vincetoxicum is one of the largest genera in Apocynaceae with recent expansion that includes former Tylophora, Biondia, and other small genera. In this study, we describe Vincetoxicum pingtaoanum sp. nov., a new woody species of Apocynaceae from the Three Gorges District in Central China based on our recent field and old herbarium collections. It is unique due to its growth habit and leaf characteristics which is similar to the former Biondia species. However, it has the well-developed corona common to the former Tylophora species. Diagnostic characteristics, a full description, photographs, ecology, and a distribution map and conservation status of the new species are provided in this study. Detailed comparisons with similar species and a key to all known species of Vincetoxicum from the Three Gorges District are also provided.